A Case of Urinary Bladder Urothelial Carcinoma with Squamous, Glandular, and Plasmacytoid Differentiation - Makise, Naohiro (S. Karger AG, 2014)
We report an extremely rare case of urothelial carcinoma (UC) of the urinary bladder with diverse histological differentiation into squamous, glandular, and plasmacytoid components. A 65-year-old man presented with gross hematuria. Cystoscopy showed a papillary-growing tumor with a wide-based stalk on the left wall of the urinary bladder. Based on the clinical diagnosis of locally invasive bladder cancer, the patient underwent radical cystectomy. Histological examination of the cystectomy specimen revealed UC with histological differentiation into multiple tumor subtypes. The tumor was composed of squamous cell carcinoma with marked keratinization, adenocarcinoma characterized by tall columnar cells with scattered goblet cells, conventional high-grade invasive UC and UC in situ, and plasmacytoid UC composed of discohesive cancer cells with eccentric nuclei and eosinophilic cytoplasm that diffusely infiltrated the bladder wall through the serosal surface. Immunohistochemically, the loss of membranous E-cadherin expression was noted only in the plasmacytoid UC component. The patient developed local recurrences 2 months postoperatively and died of the disease 6 months postoperatively. It is critical to correctly diagnose the histological variants of UC to predict a patient's prognosis and to determine the optimal treatment.